Effect of Web-Based Education on Knowledge, Attitude, and Practice of Nurses in Neonatal Intensive Care Unit - Parvaneh Zamani; Afsaneh Dehnad; Hamid Haghani; Leili Borimnejad (Interdisciplinary Journal of Virtual Learning in Medical Sciences, 2019)
Background: The neuroprotective interventions are necessary for developing the brain of premature neonates. Neonatal nurses require continuing education about this subject and nowadays distance education is a possibility. Objectives: This study aimed to assess the impact of web-based teaching on knowledge, attitude, and practice of nurses in the neonatal intensive care unit. Methods: This quasi-experimental pre- and post-intervention study with a control group was conducted in 2018. A total number of 70 nurses from selected hospitals affiliated to the Iran University of Medical Sciences were assessed for their knowledge, attitude, and practice in seven neuroprotective core measures prior to the intervention. A four-week standardized training package was implemented in these hospitals through virtual classroom approach. After six weeks of post-intervention, all nurses who attended the virtual training were assessed for the same competencies using the WEE care assessment tool. The reliability of the tool was estimated by calculating the internal consistency of items (α = 0.95). The t test and repeated measures ANOVA were conducted to analyze the data using SPSS V. 16 software. Results: The findings indicated that the mean score of knowledge significantly increased (P < 0.001) in the web-based education group (21.97 ± 5.64) compared to the control group (13.94 ± 4.7). However, there was no significant difference between the two groups in the mean scores of attitude and practice. Conclusions: Web-based teaching was found to be effective in improving the knowledge of nurses; however, the results suggest that virtual teaching methods need to be developed to affect the attitude and practice of neonatal nurses.